(untitled) (Research, Society and Development, 2021)
The study aimed to analyze the attention given to health in the government plans of candidates for the position of governor of the State of Bahia, in the 2018 electoral process. This is a documentary research, with an exploratory character and quantitative and qualitative approach. Data were collected on the DivulgaCand portal of the Superior Electoral Court. For data organization and treatment, Bardin’s content analysis (2011) was used. The data were organized based on the following categories: specific projects; infrastructure; qualification of primary care; health technology; health surveillance; regionalization of assistance and comprehensive health care. When observing the number of proposals by party representation, the Partido dos Trabalhadores (PT) and Democrats (DEM) presented a greater range of subjects and volume of proposals. At the same time, there was a higher incidence of guidelines related to infrastructure and comprehensive health actions. However, the diagnosed proposals are diffuse and dissonant from the prerogatives listed in the national health guidelines.